Discovery of KV1.3 ion channel inhibitors: Medicinal chemistry approaches and challenges. Issue 4 (1st May 2021) - Gubič, Špela; Hendrickx, Louise A.; Toplak, Žan; Sterle, Maša; Peigneur, Steve; Tomašič, Tihomir; Pardo, Luis A.; Tytgat, Jan; Zega, Anamarija; Mašič, Lucija P.
Abstract: The KV 1.3 voltage‐gated potassium ion channel is involved in many physiological processes both at the plasma membrane and in the mitochondria, chiefly in the immune and nervous systems. Therapeutic targeting KV 1.3 with specific peptides and small molecule inhibitors shows great potential for treating cancers and autoimmune diseases, such as multiple sclerosis, type I diabetes mellitus, psoriasis, contact dermatitis, rheumatoid arthritis, and myasthenia gravis. However, no KV 1.3‐targeted compounds have been approved for therapeutic use to date. This review focuses on the presentation of approaches for discovering new KV 1.3 peptide and small‐molecule inhibitors, and strategies to improve the selectivity of active compounds toward KV 1.3. Selectivity of dalatazide (ShK‐186), a synthetic derivate of the sea anemone toxin ShK, was achieved by chemical modification and has successfully reached clinical trials as a potential therapeutic for treating autoimmune diseases. Other peptides and small‐molecule inhibitors are critically evaluated for their lead‐like characteristics and potential for progression into clinical development. Some small‐molecule inhibitors with well‐defined structure–activity relationships have been optimized for selective delivery to mitochondria, and these offer therapeutic potential for the treatment of cancers. This overview of KV 1.3 inhibitors and methodologies is designed to provide a good starting point for drug discovery to identify novel effective KV 1.3 modulators against this target in the future.